Thematic Dossier: Live Arts and the Anthropocene/Capitalocene I (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Information on the content of the Thematic  Dossier: Live Arts and the Anthropocene/Capitalocene I
Keywords: editorial; articles; thematic dossiers